Analysis of the Behaviour of Steel-Concrete Composite Truss - Duratna, Patricia; Bouchair, Abdelhamid; Bujnak, Jan (Communications - Scientific letters of the University of Zilina, 2011)
The design specifications of composite truss, included in the American standard (ASCE), are not covered in the European standards (Eurocodes). In this study, to investigate the behaviour of the composite trusses, a finite element model (FEM) is developed using the software CAST3M. The influence of various parameters, such as the diameter of the shear connectors, the degree of connection, the top chord section and the material characteristics on the behaviour of the composite truss and the shear connectors are analyzed. The model shows that the shear connection in the steel-concrete composite truss reduces its deflection by approximately 50 % in comparison with the steel truss. The significant influence of the top chord section on the shear forces in the shear connectors was observed.